THE ROLE OF GREEN TRUST IN MEDIATING GREEN PERCEIVED VALUE, GREEN PERCEIVED RISK ON GREEN PURCHASE INTENTION OF ELECTRIC CARS IN DENPASAR CITY - I Made Gilang Mahendra; I Gst. Ayu Kt. Giantari, I Gst. Ngurah Jaya Agung Widagda, Ni Wayan Ekawati (Adisam Publisher, 2024)
The current environmental damage is quite worrying, global warming caused by exhaust gas emissions from fossil fueled vehicles is one of the problems that endangers the environment. Electric vehicles are believed to be more environmentally friendly than fossil fuel vehicles because electric vehicles do not emit exhaust emissions. The population in this research are people in Denpasar City who intend to buy an electric car with a sample of 100 respondents through non- probability sampling. Data were collected using a questionnaire in the form of a Google form, data were processed using SEM-PLS using SmartPLS Version 3 software. The results of the analysis showed that green perceived value had a positive and significant effect on green trust and green purchase intention, green perceived risk had a negative and significant effect on green trust and green purchase intention, green trust has a positive and significant effect on green purchase intention, and green trust is able to mediate the effect of green perceived value and green perceived risk on green purchase intention.